Media Massa dan Pembentukan Pandangan Politik di Era Digital - Salwa Aidah; Aida Restu Amalia; Alifia Aqida (Indonesian Character Journal, 2026)
The rapid development of information and communication technologies has brought about fundamental changes in the landscape of contemporary political communication. Digital mass media not only function as channels for the dissemination of political information but also serve as arenas for meaning construction, narrative production, and the negotiation of political perspectives at the societal level. This study aims to analyze the role of digital mass media in shaping public political views and to examine the patterns of interaction among media institutions, political actors, and the public within the context of digital democracy. The research employs a systematic literature review method by examining relevant and reputable scholarly sources, including indexed national and international journals, academic books, research reports, and policy articles published between 2020 and 2025. The findings indicate that digital mass media exert a significant influence on the formation of public political opinion through mechanisms of framing, agenda setting, and political narrative construction. The interactive nature of digital media enables active public participation in political discourse, contributing to the emergence of more deliberative and participatory patterns of political engagement. However, this dynamic also presents serious challenges, including opinion polarization, information bias, and the spread of misinformation, which have the potential to undermine the quality of public deliberation. This study underscores the importance of strengthening media literacy and political literacy as essential prerequisites for critical and responsible political participation. Furthermore, digital mass media are expected to fulfil their ethical and normative functions by providing accurate, balanced, and contextualized information. Theoretically, this article contributes to the development of political communication studies and digital media research, while also offering practical implications for enhancing the quality of democracy in the digital era.